Tracking pre-mRNA maturation across subcellular compartments identifies developmental gene regulation through intron retention and nuclear anchoring - Yeom, Kyu-Hyeon; Pan, Zhicheng; Lin, Chia-Ho; Lim, Han Young; Xiao, Wen; Xing, Yi; Black, Douglas L. (Genome Research, 2021)
Steps of mRNA maturation are important gene regulatory events that occur in distinct cellular locations. However, transcriptomic analyses often lose information on the subcellular distribution of processed and unprocessed transcripts. We generated extensive RNA-seq data sets to track mRNA maturation across subcellular locations in mouse embryonic stem cells, neuronal progenitor cells, and postmitotic neurons. We find disparate patterns of RNA enrichment between the cytoplasmic, nucleoplasmic, and chromatin fractions, with some genes maintaining more polyadenylated RNA in chromatin than in the cytoplasm. We bioinformatically defined four regulatory groups for intron retention, including complete cotranscriptional splicing, complete intron retention in the cytoplasmic RNA, and two intron groups present in nuclear and chromatin transcripts but fully excised in cytoplasm. We found that introns switch their regulatory group between cell types, including neuronally excised introns repressed by polypyrimidine track binding protein 1 (PTBP1). Transcripts for the neuronal gamma-aminobutyric acid (GABA) B receptor, 1 (Gabbr1) are highly expressed in mESCs but are absent from the cytoplasm. Instead, incompletely spliced Gabbr1 RNA remains sequestered on chromatin, where it is bound by PTBP1, similar to certain long noncoding RNAs. Upon neuronal differentiation, Gabbr1 RNA becomes fully processed and exported for translation. Thus, splicing repression and chromatin anchoring of RNA combine to allow posttranscriptional regulation of Gabbr1 over development. For this and other genes, polyadenylated RNA abundance does not indicate functional gene expression. Our data sets provide a rich resource for analyzing many other aspects of mRNA maturation in subcellular locations and across development.
10.1101/gr.273904.120